Visco-thermal and structural characterization of water chestnut flour - Hussain, Syed Zameer (J Food Sci Technol, 2020)
In order to increase flour recovery, resistant starch content and to lower the glycemic index and glycemic load, the water chestnuts were subjected to pre-optimized conditions of pre-conditioning. The low glycemic index water chestnut flour (F1) obtained thereafter was analyzed for different functional, viscous, thermal and structural properties. F1 exhibited improved functional properties due to gelatinization of starch followed by retrogradation during pre-conditioning which confirms its feasibility for development of diverse food products in comparison to commercially available market flour (F2). Pasting properties—peak viscosity, hold viscosity, breakdown viscosity, final viscosity and set back viscosity (SBV) were found significantly (p < 0.01) higher in case of F1 than F2. Higher peak viscosity of F1 can be accorded to its higher swelling capacity than F2. Further, higher SBV of F1 suggests its susceptibility towards retrogradation and gel formation. Differential scanning calorimetry results revealed that gelatinization temperature, endothermic peak width, onset, peak and conclusion temperatures were significantly (p < 0.01) lower, whereas enthalpy of gelatinization and peak height index were significantly (p < 0.01) higher in case of F1 as compared to F2. Lower gelatinization transition temperatures of F1 could be attributed to its more water absorption ability than F2 which suggests its potential as a thickening agent in foods. ATR-FTIR studies revealed high absorbance ratio at 1047/1022 cm(−1) in F1 as compared to F2 which confirmed the presence of packed double helices within the starch crystalline regions in F1 sample. Scanning electron microscopy showed the smooth, plumper and fused granules in F1 whereas disintegrated granules were observed in F2.